Agile management and the Toyota way for software project - Morien, Roy (IEEE, 2005)
The history of failure of information systems development over the last 20 years is well recorded. Literally billions of dollars have been wasted on development projects that failed. The Information Systems and Technology industry (IST) has, in the main, failed to find a solution to this situation.This paper will discuss these various statements, illustrating the dismal record of failure, the underlying causes of these failures, and the history of research into alternative development approaches, now generally termed ?Agile Development Methods?. It is also proposed that Agile Development requires Agile Management, and I will discuss this concept and practice of Agile Management. This approach to managing software development projects can be seen to have roots in the Lean Manufacturing thinking and practice, derived in many respects from what is known as The Toyota Manufacturing Process. This foundation in a demonstrably successful and long-standing product development and manufacturing process gives strength and credibility to the concept and practice of Agile Development, and Agile Project Management.